Fibrillary glomerulonephritis in a human immunodeficiency virus-positive, hepatitis C-negative Indian patient: Expanding the profile of renal involvement in human immunodeficiency virus infection - Smita Mary Matthai; Anna T Valson; Neelaveni Duhli; Priscilla Rupali; Anna B Pulimood; Santosh Varughese (Wolters Kluwer Medknow Publications, 2018)
Highly active anti retroviral therapy (HAART) has dramatically improved life expectancy of human immunodeficiency virus (HIV) infected patients, converting HIV infection into a chronic illness with associated changes in its attendant renal complications. The past two decades have witnessed a decrease in the prevalence of HIV associated nephropathy (HIVAN), traditionally considered to be the hall mark of renal involvement in HIV infection. Simultaneously a host of other glomerular and tubulo-interstitial diseases have emerged, expanding the spectrum of HIV associated renal diseases, predominant among which is HIV associated immune complex mediated kidney diseases (HIVICK). Of the diverse glomerular diseases constituting HIVICK, fibrillary glomerulonephritis (FGN) remains a rarity, with only two existing reports to date, confined to patients co-infected with Hepatitis C virus (HCV). The pathogenetic role of HIV in these patients remains under a cloud because of previously well established association of HCV infection and FGN. We report a case of FGN in a HIV seropositive, HCV negative Indian patient, highlighting the diagnostic electron microscopy (EM) findings of FGN and strengthening the causal association of HIV with FGN. In view of increasing heterogeneity of renal complications in HIV infection, the diagnostic utility of a comprehensive renal biopsy evaluation inclusive of EM is emphasized for appropriate selection of treatment modalities.